Early life social conditions and adverse experiences are associated with childhood BMI and perceived overeating - Bartoskova Polcrova, Anna; Ksinan Jiskrova, Gabriela; Bobak, Martin; Pikhart, Hynek; Klánová, Jana; Ksinan, Albert J (Pediatric obesity, 2025)
BACKGROUND: Early life socioeconomic disadvantage and adverse experiences may lead to overeating, which is in turn associated with increased body mass index (BMI). However, recent evidence indicated that the association between childhood BMI and overeating might be bidirectional. This bidirectionality prompts the need for further investigation of early life predictors of BMI in childhood. OBJECTIVES: To longitudinally assess the directionality of the association between childhood BMI and perceived overeating and to investigate their antecedent early life predictors. METHODS: The sample included data from 5151 children from the ELSPAC study, collected between 18 months and 11 years of child age. The outcomes were child BMI and mother-reported overeating, assessed at the age of 3, 5, 7 and 11 years. Predictors included maternal BMI, maternal education, single parenthood, financial difficulties and adverse childhood experiences (ACEs) reported by parents and paediatricians. The random intercept cross-lagged panel model was applied. RESULTS: The mean child's BMI at age 3 was 15.59 kg/m2 and increased to 17.86 kg/m2 at age 11. The percentage of parent-reported overeating increased in the following period, from about 12% at age 3 to 17% at age 11. The results showed temporal stability in perceived overeating and BMI, with a bidirectional relationship strengthening over time. The child's BMI was associated with maternal BMI. Maternal BMI was positively associated with child-perceived overeating, but a stronger effect was found for ACEs. ACEs mediated the impact of maternal education, financial difficulties and single parenthood on overeating. CONCLUSIONS: We observed stable bidirectional associations between BMI and perceived overeating. The results indicated two main pathways: one linked to maternal BMI and early childhood BMI increase followed by perceived overeating and the second associated with ACEs mediating the effect of early childhood social factors on perceived overeating, leading to gradual BMI gain.
Keywords: Adverse Childhood Experiences; lidé; Pediatric Obesity; matky; Mothers; Infant; Female; dítě; Longitudinal Studies; Body Mass Index; Humans; index tělesné hmotnosti; obezita dětí a dospívajících; Hyperphagia; Socioeconomic Factors; předškolní dítě; Child, Preschool; mužské pohlaví; socioekonomické faktory; ženské pohlaví; hyperfagie; Male; longitudinální studie; Child; kojenec; nepříznivé zkušenosti z dětství